Poetry for Students. Presenting Analysis, Context and Criticism on Commonly Studied Poetry - Smith, Jennifer, editor 183709; Thomason, Elizabeth, editor 652229; Gale Group (Online service) 651863 (Detroit : Gale, part of Cengage Group, 2001)
Features discussion and analysis of poems of all time periods, nations, and cultures. Provides an overview of the poem and discussion of its principal themes, images, form and construction.